Strategies for Overcoming Unemployment among Freshgraduate - Agustina, Reni; Na'imah, Na'imah; Ridlo, Wildani; Sofiana, Arina Nur (Universitas Mataram, 2024)
Unemployment is one of the main problems that every country always faces. The high unemployment rate causes competition to find work to become greater, resulting in college graduates who are not yet working. The aim of this research is to overcome the problem of unemployment among fresh graduate students due to the lack of skills and employment opportunities appropriate to their major as well as the impact of Covid 19, the low skills and employment opportunities for fresh graduate students so that strategies are needed. The research method used is literature research, namely a technique for collecting data and information through various literature or references, which means collecting data by understanding theories from various relevant literature. Skilled and trained Human Resources (HR) organized in vocational villages are of course expected to be able to utilize natural resources and regional potential/advantages that are more economically valuable, competitive and provide maximum results and are able to open/create employment opportunities for themselves and others. other as an effort to eradicate educated unemployment. creating business opportunities and entrepreneurship for people who need jobs through the formation of business groups as an effort to eradicate educated unemployment through vocational village pilots with training based on regional advantages